Memorandum of understanding between Universiti Teknologi MARA and Amantronic Sdn Bhd / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.